Vivências do desejo feminino: a experiência homoafetiva - Machado, Aline Oliveira (2010)
Thinking of a society where part of the population is destined to live their affectivity in secret is to think like these people "admit to himself" a sexuality intended to marginalization and how to face, from the identification of desire itself to the practice of desire. Several studies have shown that even with the existence of social norms that shy away prejudice, discrimination is still active, although it is assuming forms of expression that do not come into direct confrontation with the term of the current standards of tolerance. These discriminatory attitudes and situations of exclusion have created feelings of inadequacy in homoerotic subjects, which is reflected directly on your self-esteem and in carrying out its duties as individuals belonging to the society. Consequently, the homoerotic subjects are seeking emotional support from each other, allowing them to soften the refusal of the harmonic coexistence with the rest of society. So the aim of this study is to investigate the construction of the social experience of the group of women who experience the practice of homoerotic desire as active minorities in a social dynamic characterized by disparaging representations to groups of sexual minorities. Describing how in this universe have developed and expressed the strategies of this experience. In this regard, research is based on five aspects: perception about the causes of homosexuality; Emotional and social factors involved the discovery of homoerotic desire; Perception about the discrimination experienced; Perception about the movements and sexual minorities contributed in the struggle for sexual diversity; and Perception about which are the flags of fights must be prioritized by the movement of sexual minorities. Two studies were carried out for this purpose, the first with sample composed of 81 women who practice the homoeroticism, contacted through networks of contacts; the second study included a sample of 176 women students of humanities courses that had already begun their sexual practice. Analyzing the data obtained in two studies, we can say that if homoerotic women have a vivid perception of the discrimination and prejudice from your homoerotic practices, consequences to which they are subject in society, on the other hand the experience of sexuality is full by feelings of social repression for straight women. Thus, discrimination is felt by this woman, and even more intensely lived by women homoerotic practice, which makes the practice of sexuality lived through the filter normative created and maintained socially.